AI AND DIGITAL PAINTING: REIMAGINING HUMAN–MACHINE COLLABORATION - P. Thara; Traisa, Roopa; Chaudhary, Swati; Modi, Priya; Saraswat, Vivek; Kalra, Hitesh; Ramtirthkar, Chandrashekhar Ramesh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
In this paper, I examine the digital transformation the artificial intelligence (AI) has on digital painting by examining how the relationship between humans and machines is changing as a new artistic creation paradigm. It follows the historical heritage of machine-assisted art, studies the underlying ground of technology of GANs, diffusion models, and reinforcement learning, and evaluates how these systems grapple with artists, in real-time feedback and adaptive learning. The paper presents case studies of such large platforms like DALL3, Midjourney, Runway ML, and Adobe Firefly to show that AI is not an independent agent, but a cognitive partner, who expands the imagination of humans and redefines authorship and aesthetic agency. The move of aesthetics toward posthuman, collective authorship, and the need to be transparent in the use and attribution of data is revealed in philosophical and ethical analyses. The conclusion of the paper will be a futuristic projection of a hybrid creative future in which human emotion and artificial cognition will come together to create a generative, ethical and interactive art ecosystem.